PENGGUNAAN EGM2008, EGM1996 DAN GPS-LEVELING UNTUK TINGGI UNDULASI GEOID DI SULAWESI - Dadan Ramdani (Pusbindiklat - LIPI, 2010)
GPS is used increasingly and commonly in the last past year in all aspect of live. But the height information in GPS is not the actual height. To convert it to actual height is needed geoid undulation. Geoid has three wavelengthsi.e. short, medium and long. From these three geoids, the long wavelength which is obtained from the global model is the important one to determinant the geoid. In 2008 Pavlis NK from NGA had established the global model (EGM2008) which has orde and degree of 2190. This global model was validated and is used to calculate the geoid undulation in Sulawesi. EGM2008 Validation was carried out with comparation between the geoid undulation of EGM2008 and EGM1996 with the geoid undulation from GPS-Leveling’s observation data. The result of this validation shows that EGM2008 in Sulawesi has better results compare with EGM1996. The standard deviation of EGM2008 is 0.88 cm better than EGM1996.